(untitled) (Nepalese Journal of Management Research, 2025)
This study explores the influence of perceived behavioral factors on investment decisions in the Nepalese Stock Market (NEPSE). It assesses whether heuristic behaviors, prospect theory, market variables, and herding influence investment decisions and performance. A sample of 350 investors was selected using a random sampling technique, and data were collected through structured questionnaires. The study uses descriptive and analytical research designs to analyze the relationship between behavioral factors and investment decisions. The results show that heuristic variables, such as reliance on personal expertise and trend-following, significantly impact investment performance. However, prospect and market variables and herding behavior exhibit no significant effect on investment outcomes. The study highlights that while investors often depend on cognitive shortcuts, numerous unexplored factors influence their performance. This research offers valuable insights for policymakers, investors, and market analysts seeking to understand the behavioral drivers in emerging markets like Nepal.